A single-machine scheduling problem with a deterioration model and partial maintenance. Issue 8 (30th November 2018) - Hou, Yung-Tseng; Yang, Dar-Li; Kuo, Wen-Hung; Wu, Li-Shing
Abstract: In realistic situations, a machine can be restored to its original state after complete maintenance. However, sometimes, in order to save time, a machine may just be maintained to an available state and then it is put back to a production system. Such maintenance is called "partial maintenance". Partial maintenance usually takes shorter time than complete maintenance. However, a machine in such an available state is not as efficient as a new one. Therefore, it is a trade-off between to save maintenance time and to get machine efficiency in some scheduling problems. In this paper, we propose a partial maintenance model and incorporate it into a single-machine scheduling problem with a deterioration model. The objective is to find a schedule with an appropriate maintenance strategy to minimize the makespan.